Outcomes of allogeneic hematopoietic stem cell transplantation in R/R DLBCL patients with failure of CAR-T therapy - Mengya Cong; Sicheng Ai; Liqing Kang; Mao Jin; Ying Zhu; Caixia Li; Zhengming Jin; Lei Yu; Depei Wu; Haiwen Huang (Experimental Hematology & Oncology, 2024)
Abstract From October 2017 to June 2022, we retrospectively report outcomes of R/R DLBCL patients with failure of CAR-T therapy, then receiving allo-HSCT. Among 10 patients, 5 were males and 5 females, with a median age of 43.5 (27–52) years. All patients were diagnosed refractory/relapsed diffuse large B cell lymphoma. The median time from CAR-T treatment to transplantation was 84.5 (31–370) days. The median follow-up was 21 (3–69) months. 5/10 patients attained CR and 1/10 patient attained PR during the follow up. The objective response rate (ORR) was 60%. The 1-year overall survival (OS) and progression-free survival (PFS) were 70% and 40%, respectively. At the time of the analysis, 6 patients were still living. During the follow up, four patients have died and the causes were disease relapses and progressions (2 patients), acute renal failure (1 patient), severe pulmonary infection (1 patient). Non-relapse was 20.0%.